Synergetic Chemistry and Interface Engineering of Hydrogel Electrolyte to Strengthen Durability of Solid‐State Zn–Air Batteries. Issue 2 (16th December 2021) - Tang, Kun; Fu, Jimin; Wu, Mingzai; Hua, Tao; Liu, Jun; Song, Li; Hu, Haibo
Abstract: For the challenging pursuit of high energy efficiency and mechanical tolerance in flexible solid‐state Zn‐air batteries (FSZABs), a hydrogel electrolyte (HE) consisting of dual‐network crosslinked polyacrylic acid‐Fe 3+ ‐chitosan (PAA‐Fe 3+ ‐CS) polymer host infiltrated with a mixed aqueous electrolyte of NH4 Cl and ZnCl2 is developed. The absorbed near‐neutral electrolyte renders the HE high ionic conductivity but low corrosiveness to both electrocatalysts and Zn metal anode (ZMA), ensuring more stable Zn‐OH‐O2 chemistry compared to that in strong alkaline electrolyte and thus endowing the assembled FSZABs with a landmark cycle life up to 120 h (5 mA cm −2 ). More intriguingly, the CS molecular beams introduced into the PAA hydrogel backbone will precipitate and fold subjecting to the Hofmeister effect when saturated with the near‐neutral electrolyte, which can effectively enhance the interfacial adhesion strength of the HE on both air cathode and ZMA, achieving reliable and robust bonding between them. Thus, the FSZABs simultaneously exhibited a superior tolerance to repeated mechanical deformation during operation, allowing more than 360 continuous bending‐recovery cycles without any decline in voltage efficiency. The ingenious chemistry and interface synergetic engineering on the crucial HEs provides a rational methodology to realize boosted electrochemical and mechanical durability of FSZABs forward for future practical implementation. Abstract : Polyacrylic acid‐Fe 3+ ‐chitosan/NH4 Cl dual network hydrogel electrolyte (HE) is developed. The interface toughness of the HE on both carbon cloth and Zn foil is tremendously enhanced by the shrinkage of the HE matrix stemming from the bundling of precipitated chitosan macromolecules driven by the Hofmeister effect, which significantly strengthens the electrochemical and mechanical durability of the assembled flexible solid‐state Zn‐air batteries.